2015
DOI: 10.1109/tasc.2014.2385932
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Finite-Element Models of Persistent-Current Effects in Nb<sub>3</sub>Sn Accelerator Magnets

Abstract: Persistent magnetization currents are induced in superconducting filaments during the current ramping in magnets. The resulting perturbation to the design magnetic field leads to field quality degradation, in particular at low field where the effect is stronger relative to the main field. The effects observed in NbTi accelerator magnets were reproduced well with the criticalstate model. However, this approach becomes less accurate for the calculation of the persistent-current effects observed in Nb3Sn accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Furthermore, experiments on Nb3Sn thin films [85] showed that if Nb3Sn grain sizes were Since magnetization is the driving force for low-field flux jumps and field errors in magnets, decreasing the low-field Jc by shifting the Fp(B) curve peak to 0.5Bc2 also benefits in improving low-field stability and suppressing the field errors caused by persistent-current magnetization [10,86].…”
Section: Prospects To Improve Pinning Capacitymentioning
confidence: 99%
“…Furthermore, experiments on Nb3Sn thin films [85] showed that if Nb3Sn grain sizes were Since magnetization is the driving force for low-field flux jumps and field errors in magnets, decreasing the low-field Jc by shifting the Fp(B) curve peak to 0.5Bc2 also benefits in improving low-field stability and suppressing the field errors caused by persistent-current magnetization [10,86].…”
Section: Prospects To Improve Pinning Capacitymentioning
confidence: 99%
“…Magnetic measurements of MQXFS1a were performed with Printed Circuit Board (PCB) rotating coil probes [5], the technique having been validated throughout the HQ magnetic measurement program [6,7]. These PCB probes are of radial type, with 5 different loops (one is a spare) side to side across the board, each with 12 turns per layer, and trace separation 0.35mm.…”
Section: Probes and Measurement Systemsmentioning
confidence: 99%
“…In particular, a 0.8 mm strand of the RRP 54/61 or 60/61 design was chosen for the HD models since it provided the best critical current performance. This layout, however, has a large effective filament diameter, which results in limited stability margins, and significant field distortions due to conductor magnetization (Wang et al 2015). New wire architectures with a higher number of sub-elements should be implemented to increase the strand diameter and extend the design to a larger aperture while reducing the effective filament size (Sabbi et al 2016).…”
Section: Discussionmentioning
confidence: 99%